PENGIMPLEMENTASIAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN IPS DI KELAS INKLUSI SMP NEGERI 39 SEMARANG - Azizah, Winda Nur; Lestari, Puji (Universitas Negeri Semarang, 2021)
SMP Negeri 39 Semarang is one of the inclusion schools in the city of Semarang. For its existence, it must be supported by curriculum development and learning, including in character education. Inclusion schools are considered to be the right means of implementing character education because of the mixing process between children with special needs and regular children in the same class. The implementation of character education can be done through learning, one of which is through social studies learning. The role of IPS is considered to be able to implement character values ​​for students so that students are able to adapt to the environment with several good characters from themselves. The purpose of this study (1) To explain the implementation of character education in SMP Negeri 39 Semarang. (2) Carry out the implementation of character education into social studies learning in the inclusion class of SMP Negeri 39 Semarang. (3) Inhibiting and driving factors in implementing character education in social studies learning in the inclusion class of SMP Negeri 39 Semarang. The method used in this research is descriptive qualitative with data collection techniques using observation, interviews and, documentation. The location of this research is SMP Negeri 39 Semarang. The subjects of this study were school principals, curriculum staff, social studies teachers in inclusive classes and students. The validity test of this data uses triangulation of sources and techniques or methods. The analysis technique used is the stage of data collection, data reduction, data presentation, and conclusion. The results of this study indicate that SMP Negeri 39 Semarang implements character education into all activities in the school. (1) The implementation of character education in this school is carried out through learning activities, familiarization activities or school culture and self-development activities. (2) The implementation of character education into social studies learning in the inclusive class is carried out through the planning, implementation and evaluation stages which are all integrated with character education. (3) There are driving factors in the implementation of character education including supporting facilities and infrastructure, supporting school programs, and human resources who take part in implementing character values. The inhibiting factor is the existence of the corona pandemic virus, the lack of integration of character education at school and at home, the lack of parties who supervise the behavior and character of students. SMP Negeri 39 Semarang merupakan salah satu sekolah inkusi di Kota Semarang. Sekolah inklusi dianggap sarana yang tepat dalam pengimplementasian pendidikan karakter. Pengimplementasian pendidikan karakter dapat dilakukan melalui pembelajaran IPS agar peserta didik mampu beradaptasi dengan lingkungan dan berbekal karakter yang baik. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan teknik pengumpulan data menggunakan observasi, wawancara dan, dokumentasi. Hasil penelitian ini menunjukkan bahwa (1) Pengimplementasian pendidikan karakter di sekolah ini dilakukan melalui kegiatan pembelajaran, kegiatan pembiasaan dan kegiatan pengembangan diri. (2) Pengimplementasian pendidikan karakter ke dalam pembelajaran IPS di kelas inklusi dilakukan melalui tahap perencanaan, pelaksanaan dan evaluasi yang semuanya terintegrasi dengan pendidikan karakter. (3) Ditemukan faktor pendorong dalam pengimplementasian pendidikan karakter yakni sarana dan prasarana mendukung, program sekolah mendukung, dan sumber daya manusia yang ikut andil dalam pengimplementasian nilai karakter. Faktor penghambatnya adanya pandemi virus corona, kurang terintegrasinya pendidikan karakter di sekolah dengan di rumah, kurangnya pihak yang mengawasi perilaku dan karakter peserta didik.